Determination of Trace Heavy Metal Ions by Flame Atomic Absorption Spectrometry after Preconcentration with Manual-Controlled Injection Nano-Calcium Titanate Enricher - Zhang, D.; Zhang, W.J.; Hou, P. (Asian Journal of Chemistry, 2011)
A new method has been developed for the determination of trace lead, cadmium, zinc, nickel and silver ions based on separation and preconcentration with a manual-controlled injection nano-calcium titanate enricher (MINTE) prior to their determination by flame atomic absorption spectrometry. The optimum experimental parameters for preconcentration of the heavy metals studied, such as pH, flow rate and volume, eluent and interfering ions, have been investigated. The results showed that all the heavy metals studied could be quantitatively retained by MINTE in the pH range of 5-9 and then eluted completely with 2 mol L-1 HNO3. The detection limits of this method for lead, cadmium, zinc, nickel and silver ions were 32, 5, 4.1, 9.4 and 7 ng L-1, respectively. The method has been applied to the simultaneous determination of trace amounts of lead, cadmium, zinc, nickel and silver ions in water samples with satisfactory results.